Method for producing carbon dioxide gas-immobilizing material
By setting a reduction atmosphere in the electric furnace and heat treatment of raw materials containing CaO and SiO2, the dependence on high-purity raw materials and CO2 emission problems in the prior art are solved, and efficient production of γ-type dicalcium silicate and CO2 absorption effects are achieved.
Patent Information
- Application Number
- CN202380056673.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-02
- Filing Date
- 2023-08-01
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art requires high purity CaO and SiO2 raw materials when manufacturing gamma dicalcium silicate, and additional CO2 emissions may be generated during the heat treatment process, limiting the industrial production of materials and CO2 reduction capabilities.
By setting a reduction atmosphere in the electric furnace, the raw materials containing CaO and SiO2 are heat treated to generate gamma dicalcium silicate, and industrial by-products such as steel slag, fly ash, etc. are used as raw materials to increase the impurity content of the material, but efficient CO2 absorption materials can still be generated through appropriate correction and treatment.
The CO2 discharge amount is significantly reduced when manufacturing gamma-type dicalcium silicate, and the low-purity CaO and SiO2 raw materials can be effectively utilized, which improves the CO2 absorption capacity of the material and the feasibility of industrial production.
Smart Images

Figure BDA0005258032120000061 
Figure BDA0005258032120000071 
Figure BDA0005258032120000081
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a carbon dioxide gas fixing material. Background Art
[0002] Decarbonization is required in various industries. On October 26, 2020, at the 203rd extraordinary session of the National Assembly, it was announced that "the goal is to achieve carbon neutrality and a decarbonized society by 2050." In addition, at the Climate Summit hosted by the Global Warming Countermeasures Promotion Headquarters and the United States on April 22, 2021, it was announced that the goal is to reduce greenhouse gases by 46% from 2013 by 2030, and then continue to challenge the height of 50%. Against this background, CO2 reduction technology has attracted more attention than ever before. In particular, carbon-negative materials are urgently needed to be developed. Here, carbon negativity refers to a state in which the amount of CO2 absorbed is greater than the amount of CO2 emitted.
[0003] Conventionally, as a carbon-negative carbon dioxide gas fixation material, for example, γ-type dicalcium silicate produced by using slaked lime produced as a by-product when acetylene is produced from calcium carbide as a raw material is known (for example, see Patent Documents 1 to 3). These γ-type dicalcium silicates can significantly reduce the amount of CO2 emitted from the raw material, and the basic unit of CO2 emission during the production of γ-type dicalcium silicate can be set to 200 kgC / t or less.
[0004] Patent Document 1: Japanese Patent No. 05867929
[0005] Patent Document 2: Japanese Patent No. 05914492
[0006] Patent Document 3: Japanese Patent No. 06057389
[0007] However, in this method, unless a CaO raw material or a SiO2 raw material with a high purity is used as a raw material, γ-type dicalcium silicate cannot be produced, and there is a problem that the amount that can be produced industrially is limited. In addition, since these γ-type dicalcium silicates are heat-treated by using a rotary kiln and a burner to boil fuel, even if the CO2 emission from the raw material is reduced, CO2 emission caused by the combustion of the fuel may still be generated.
[0008] If a method can be established to produce γ-type dicalcium silicate using CaO raw materials and SiO2 raw materials containing a large amount of impurities, in addition to the by-product slaked lime, industrial by-products such as concrete raw material sludge, coal ash, fly ash, and various slags (blast furnace slag, converter slag, electric furnace slag, stainless steel slag) can also be used as raw materials. In addition, nowadays, the demand for carbon-negative materials to improve CO2 reduction capabilities is increasing. It is believed that unless such carbon-negative materials are developed, it will be difficult to achieve the 2050 carbon neutrality declaration. Summary of the invention
[0009] The present invention is made to solve the above-mentioned problems of the prior art, and its object is to provide a method for producing a carbon-negative carbon dioxide gas fixation material that has a higher effect of reducing CO2 emissions than before.
[0010] The present inventors have conducted intensive studies to achieve the above-mentioned object and have found that the above-mentioned problems can be solved by heat-treating a predetermined raw material in a reducing atmosphere in an electric furnace.
[0011] The present invention is based on the above-mentioned findings, and its gist is as follows.
[0012] [1] A method for producing a carbon dioxide gas fixation material, comprising heat treating a raw material containing a CaO source and a SiO2 source in an electric furnace whose interior is set to a reducing atmosphere.
[0013] [2] The method for producing a carbon dioxide gas fixation material according to [1], wherein the raw material contains industrial by-products, and the amount of impurities on a dry matter basis corrected by loss on ignition of the industrial by-products is 5% by mass or more.
[0014] [3] A method for producing a carbon dioxide gas fixation material according to [2], wherein the impurity is a chemical component labeled with an oxide and is at least one of Fe2O3, Al2O3, MgO, TiO2, Na2O, K2O, MnO, and SO3.
[0015] [4] The method for producing a carbon dioxide gas fixation material according to [2] or [3], wherein the industrial by-products include by-produced calcium hydroxide and / or fly ash.
[0016] [5] The method for producing a carbon dioxide gas fixation material according to any one of [1] to [4], wherein the raw material contains steel slag.
[0017] [6] The method for producing a carbon dioxide gas fixation material according to any one of [1] to [5], wherein the electric furnace is operated using renewable energy.
[0018] [7] The method for producing a carbon dioxide gas fixation material according to any one of [1] to [6], wherein the carbon dioxide gas fixation material contains 25% by mass or more of γ-type dicalcium silicate.
[0019] According to the present invention, a method for producing a carbon-negative carbon dioxide gas fixation material can be provided, which can achieve a higher effect of reducing CO 2 emissions than conventional methods during production. DETAILED DESCRIPTION
[0020] Hereinafter, a method for producing a carbon dioxide gas fixation material according to one embodiment (this embodiment) of the present invention will be described. In addition, "part" and "%" used in this specification are by mass unless otherwise specified.
[0021] First, the carbon dioxide gas fixation material manufactured in the present embodiment refers to a general term for materials that can chemically fix carbon dioxide (CO2) under normal temperature. As a chemical component that can be chemically fixed, a CaO component can be cited, and a compound containing the CaO component is used. This is based on the mechanism that the CaO component in the above-mentioned compound reacts with CO2 to form CaCO3 and is chemically fixed. For example, as a carbon dioxide gas fixation material containing a CaO component, it is preferred to contain γ-type dicalcium silicate (hereinafter, sometimes referred to as "γ-C2S"). γ-C2S is a material known as a low-temperature phase in a compound represented by 2CaO·SiO2, and is completely different from α-2CaO·SiO2, α'-2CaO·SiO2, and β-2CaO·SiO2 (β-C2S) as high-temperature phases. They are all represented by 2CaO·SiO2, but have different crystal structures and densities.
[0022] In the present invention, in addition to the above-mentioned γ-C2S, tricalcium silicate (3CaO·SiO2), monocalcium silicate (α-wollastonite), calcite, calcite (calcite-magnesium calcite solid solution), calcium magnesium silicate such as calcite, etc. can also coexist, and when coexisting with γ-C2S, they can effectively function as carbon dioxide gas fixation materials. On the other hand, when coexisting with β-C2S, the performance as a carbon dioxide gas fixation material cannot be exerted.
[0023] γ-C2S is accompanied by a pulverization phenomenon called dusting during production, so compared with other compounds, less energy is required for crushing, and the carbon dioxide gas fixation effect is greater over a long period of time, so it is suitable as a carbon-negative carbon dioxide gas fixation material.
[0024] The content of γ-C2S in the carbon dioxide gas fixing material is preferably 25% by mass or more, more preferably 40% by mass or more.
[0025] Powder X-ray diffraction (XRD) can be used to identify γ-C2S, β-C2S, etc. in the carbon dioxide gas fixation material. Based on the identification results, γ-C2S, β-C2S, etc. can be quantified by the Rietveld method.
[0026] The carbon dioxide gas fixing material is obtained by a production method in which a raw material including a CaO source and a SiO 2 source is subjected to a heat treatment in an electric furnace whose interior is set to a reducing atmosphere.
[0027] The reducing atmosphere refers to a gas composition having a lower oxygen concentration than the gas composition of the atmosphere, and the oxygen concentration is preferably 10% by volume or less, and more preferably 5% by volume or less. In order to achieve such a state, it is effective to include a reducing gas such as CO gas in the electric furnace, and it is preferred that the CO gas concentration be set to about 1 to 10% by volume in a nitrogen atmosphere.
[0028] As an electric furnace, there is no particular limitation as long as the atmosphere can be set to a reducing atmosphere, and a known electric furnace can be used. From the viewpoint of the effect of reducing CO2 emissions, it is preferred that a carbon electrode be used as the electrode. In addition, from the same viewpoint, it is preferred to use carbon in the furnace body.
[0029] Examples of raw materials containing a CaO source and a SiO2 source include a mixture obtained by mixing a CaO raw material containing CaO and a SiO2 raw material containing SiO2 as a chemical composition, a raw material containing both CaO and SiO2 as a chemical composition, and a mixed raw material thereof.
[0030] It is preferred that the mixing ratio of the raw materials be adjusted to a ratio that generates γ-C2S.
[0031] Examples of the CaO raw material include calcium carbonate such as limestone, calcium hydroxide such as slaked lime, etc. Examples of the SiO2 raw material include silica, clay, etc.
[0032] In this embodiment, industrial raw materials can be used as the raw materials mentioned above, but industrial by-products can also be used. As industrial by-products, by-product calcium hydroxide, fine powder generated from waste concrete blocks, steel slag, various silicon dioxide dusts generated as industrial by-products represented by silica fume and fly ash, etc. are listed, and they can be used in place of part or all of the industrial raw materials.
[0033] Industrial by-products are exemplified below.
[0034] (Byproduct calcium hydroxide)
[0035] The by-product calcium hydroxide (also referred to as by-product slaked lime) of the present embodiment refers to the general term for calcium hydroxide produced as an industrial by-product. For example, calcium hydroxide produced as a by-product in the process of generating acetylene from calcium carbide is listed. In the by-product calcium hydroxide, for example, the purity of calcium hydroxide is about 95%, and impurities are contained in a range of less than 5%.
[0036] (Fly ash)
[0037] The fly ash in this embodiment refers to a byproduct generated from thermal power generation, and is a general term for coal ash and fly ash. In the present invention, coal ash having a large amount of unburned carbon and being difficult to utilize effectively can also be utilized.
[0038] (Steel slag)
[0039] The steel slag in this embodiment refers to the general term for blast furnace slag (granulated slag, slow-cooled slag), converter slag, electric furnace slag, and stainless steel slag. Blast furnace slag refers to a by-product produced when pig iron is produced in a blast furnace. There are granulated blast furnace slag that is vitrified by rapid cooling with water and slow-cooled blast furnace slag that is crystallized by slow cooling. Converter slag refers to a by-product produced in the converter process of refining the pig iron obtained in the blast furnace. Electric furnace slag refers to the general term for slag produced when iron is obtained by collecting waste and reducing it in an electric furnace. There are electric furnace oxidation period slag and electric furnace reduction period slag. Stainless steel slag refers to the general term for slag produced when stainless steel is produced. In this embodiment, all can be used.
[0040] In the present embodiment, the raw materials including the CaO source and the SiO2 source are industrial byproducts, and even if the impurity amount on a dry basis corrected by the loss on ignition is 5% or more, γ-type dicalcium silicate can be obtained. Although the coexisting compounds increase due to the increase in impurities (the purity of γ-type dicalcium silicate decreases), γ-type dicalcium silicate can be generated even if the impurities are about 20%. Due to the generation of this compound, dust can be induced and pulverized. By pulverization, the specific surface area becomes higher, which is useful as a CO2 absorbent. Even if the chemical composition is the same, when γ-type dicalcium silicate is not generated (when β-type dicalcium silicate is generated), it does not cause pulverization and becomes a block, so it is useless as a CO2 absorbent. As impurities, for example, as a chemical component marked with an oxide, at least one of Fe2O3, Al2O3, MgO, TiO2, Na2O, K2O, MnO, and SO3 is listed.
[0041] The total amount of the impurities on a dry basis is preferably 5 to 30%. The dry basis can be corrected by loss on ignition (LOI). Specifically, it is expressed as a relative value when the mass obtained by subtracting the loss on ignition is set to 100.
[0042] In addition, from the viewpoint of productivity and carbon negativity, the CaO content on a dry basis corrected by the loss on ignition is preferably 30 to 70%, more preferably 40 to 60%.
[0043] In this embodiment, the CO2 absorbent can be manufactured by placing the raw materials into an electric furnace, melting them by heating, discharging them, and cooling them. The raw materials do not need to be mixed or crushed, and can be simply weighed and placed in the electric furnace. In order to melt them and perform a liquid phase reaction, the raw materials do not need to be finely crushed.
[0044] When there is a powdery raw material, from the viewpoint of preventing dust generation and blowing during heating, the raw material may be put into the electric furnace after being granulated or agglomerated.
[0045] The heat treatment temperature is preferably in the range of 1400 to 1800° C., more preferably 1500 to 1700° C. After melting, the reaction is allowed to proceed for a certain period of time, and the melt is discharged from the furnace and cooled. The cooling is not particularly limited as long as it is not super-quenching, but slow cooling is preferred.
[0046] When the above raw materials are heat-treated in an electric furnace to produce a carbon-negative carbon dioxide gas fixation material, the electric furnace can be operated using renewable energy, thereby further reducing the basic unit of CO2 emission when producing the CO2 absorbent.
[0047] Renewable energy can be hydroelectric power generation, solar power generation, wind power generation, biomass power generation, geothermal power generation, etc. Hydroelectric power generation, solar power generation, and wind power generation are particularly preferred. By using renewable energy, CO2 emissions from energy can be reduced.
[0048] Example
[0049] Hereinafter, the present invention will be specifically described by way of Examples, but the present invention is not limited to these Examples.
[0050] [Example 1]
[0051] The raw materials shown in Table 1 were used to prepare the blending materials shown in Table 2. The blending materials in Table 2 were subjected to heat treatment using a rotary kiln and heat treatment using an electric furnace, the generated compounds were confirmed by XRD, the presence of dust was confirmed by visual observation, and the CO2 absorption was evaluated. The results are shown in Table 3.
[0052] Heat treatment in a rotary kiln: A kiln from Denka Co., Ltd. was used. In the raw material preparation, the raw materials were mixed and pulverized with a ball mill to an average particle size of about 15 μm. The firing temperature was controlled at the burning point of the burner and was performed at 1450 to 1500°C.
[0053] Heat treatment based on electric furnace: The electric furnace in the Qinghai plant of Denka Co., Ltd. was used. The mixed pulverization process for raw material preparation was not performed. The melting temperature was set to 1650°C. In addition, a furnace body using carbon electrodes and carbon was operated. The exhaust gas composition after stable operation was measured. Regarding the gas composition, nitrogen was 80% by volume, oxygen was 10% by volume, H2O was 7% by volume, and CO was 2% by volume.
[0054] [Table 1]
[0055] [Table 1]
[0056]
[0057] [Table 2]
[0058] [Table 2]
[0059]
[0060] In the above table, CH is by-product slaked lime, FA is fly ash, BFS is granulated blast furnace slag, LOI is the loss (mass %) when burned at 1000°C, and the total amount of impurities is the sum of Fe2O3, Al2O3, MgO, TiO2, Na2O, K2O, MnO, and SO3 as chemical components marked with oxides.
[0061] In addition, the ratio of each impurity is calculated|required according to JIS R 5202.
[0062] [Table 3]
[0063]
[0064] · Presence or absence of dust and physical form: A 90 μm pass rate of 50% or more was considered to be dusty, and a pass rate of less than 50% was considered to be dust-free. In addition, the physical form was evaluated by visual observation of the morphology of the product after production.
[0065] CO2 absorption: The carbon dioxide absorption of the obtained products was calculated by carbonating them for 7 days in air with a carbon dioxide concentration of 5%, a temperature of 30°C, and a relative humidity of 60%. In addition, considering that the sample before carbonation contains carbon dioxide, the CO2 absorption was calculated by the following formula.
[0066] (CO2 absorption amount) = (CO2 amount of the sample after carbonation treatment) - (CO2 amount of the sample before carbonation treatment)
[0067] In addition, the amount of carbon dioxide in the above formula is determined by inorganic total carbon analysis (Coulomatic-C).
[0068] According to this embodiment, γ-C2S is generated even when there are a lot of impurities, about 20%, to obtain a powdery CO2 absorbent with high activity. In the existing kiln method, γ-C2S is not generated, and a small stone-like molten mass is formed, which has a low CO2 absorption capacity.
[0069] Here, chalcedony refers to a solid solution of chalcedony and magnesia chalcedony.
[0070] [Example 2]
[0071] The basic unit of CO2 emission involved in the production of CO2 absorbent was calculated. Using the compounding material 1 shown in Table 2, a comparative study of heat treatment using a rotary kiln and heat treatment using an electric furnace was conducted. The results are shown in Table 3.
[0072] Heat treatment based on rotary kiln: A kiln from Denka Co., Ltd. is used and operated by purchasing electricity. The process is carried out in the order of (i) raw material preparation, (ii) granulation, (iii) firing, and (iv) cooling. First, (i) in raw material preparation, the raw materials are mixed and crushed to an average particle size of about 15 μm using a ball mill. This is because the raw materials need to be finely crushed in order to carry out a solid-phase reaction. At this time, electricity is consumed. (ii) Electricity is also consumed in the granulation process. (iii) Electricity and fuel are consumed in the firing process. Firing is managed at the burning point temperature of the burner, which is 1450°C to 1500°C. (iv) Electricity is consumed in the cooling process.
[0073] The electric furnace in the Qinghai plant of Denka Co., Ltd. is used for operation using electricity from hydroelectric power (renewable energy). The production is carried out in the order of (i) raw material input, (ii) heating and melting treatment, and (iii) discharge / cooling. In the electric furnace method, unlike the kiln method, there is no need for mixed pulverization for raw material preparation. This is to carry out liquid phase reaction to melt it. Electricity is consumed in the order of (i) to (iii). Melting is carried out at 1650°C. In addition, carbon electrodes and carbon furnace bodies are used during operation, and the loss of these carbon materials is investigated and converted into CO2 emissions.
[0074] Here, the following numbers are used as basic units for each CO2 emission amount.
[0075] Electricity: 0.407kgCO2 / kWh, however, ignoring renewable energy.
[0076] Fuel: 3.03kgCO2 / L
[0077] Carbon material: Multiply the loss by 3.667 to convert C (molar mass: 12) into CO2 (molar mass: 44).
[0078] [Table 4]
[0079] [Table 4]
[0080]
[0081] According to this embodiment, the basic unit of CO2 emission when manufacturing CO2 absorbent can be significantly reduced to 22kgCO2 / t. Compared with the case of cement manufacturing, the conventional kiln method is also a smaller value, but compared with this embodiment, it is a value one digit larger.
Claims
1. A method for producing a carbon dioxide gas fixation material, wherein: In an electric furnace whose interior is set to a reducing atmosphere, a raw material including a CaO source and a SiO 2 source is heat-treated.
2. The method for producing a carbon dioxide gas fixing material according to claim 1, wherein: The raw material contains industrial by-products, and the amount of impurities on a dry basis corrected by loss on ignition of the industrial by-products is 5% by mass or more.
3. The method for producing a carbon dioxide gas fixing material according to claim 2, wherein: The impurity is a chemical component marked with oxides, and is at least any one of Fe2O3, Al2O3, MgO, TiO2, Na2O, K2O, MnO, and SO3.
4. The method for producing a carbon dioxide gas fixing material according to claim 2, wherein: The industrial by-products include by-produced calcium hydroxide and / or fly ash.
5. The method for producing a carbon dioxide gas fixing material according to claim 1 or 2, wherein: The raw material includes steel slag.
6. The method for producing a carbon dioxide gas fixing material according to claim 1 or 2, wherein: The electric furnace is operated using renewable energy.
7. The method for producing a carbon dioxide gas fixing material according to claim 1 or 2, wherein: The carbon dioxide gas fixing material contains 25 mass % or more of γ-type dicalcium silicate.
Citation Information
Patent Citations
Driving transmitter of hot dip plating device
JP1994057389A